Public psychology and holistic approaches to prevention and treatment of depression - Patterson, Elissa H.; Miller, Chazlyn; Hannapel, Madison (Frontiers in Psychiatry, 2025)
It has been known since ancient times that the mind, body, and social connection are intertwined to promote thriving. More specifically, the basic pillars of health and wellbeing have been described across cultures, and they are codified in modern healthcare as the principles of lifestyle medicine. However, across the globe, emotional despair, loneliness, and chronic diseases have been rising despite a wealth of knowledge about the elements that promote happy, healthy individuals and communities. Depression has been identified as a significant element of the global mental health crisis. We know that depression is a multifaceted condition influenced by biological, psychological, social, environmental, and spiritual factors, but prevailing medical models prioritize medication and overshadow the importance of the other facets. In healthcare, pharmaceutical companies comprise a major portion of innovation that has led to the development of invaluable life-saving medications. However, some psychiatric drug makers use marketing methods rather than the scientific method to test and promote the sale of drugs to treat depression. For example, a confidential data ownership and transfer agreement that came to light during litigation over an antidepressant drug, stated that the purpose of the data collected by the drug company sponsored research was to market their product. The public and the medical community have been led to believe that drugs are more scientifically valid than other approaches to depression. We suggest a more holistic approach to prevention and treatment of emotional despair and depression, an approach that uses a public psychology lens to promote societal wellbeing.